Experimental and numerical investigation of the heat transfer between a high temperature reactor pressure vessel and the outside of the concrete confinement structure - Van der Merwe, David-John (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.